2001
DOI: 10.1094/mpmi.2001.14.3.358
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Benefit to Sugarcane Plant Growth and 15N2 Incorporation Following Inoculation of Sterile Plants with Acetobacter diazotrophicus Wild-Type and Nif¯ Mutant Strains

Abstract: The ability of the nitrogen-fixing bacterial endophyte Acetobacter diazotrophicus strain PAl5 to enhance the growth of sugarcane SP70-1143 was evaluated in the growth chamber, greenhouse, and field by comparing plants inoculated with wild-type and Nif mutant MAd3A in two independent experiments. The wild-type and Nif mutant strains colonized sugarcane plants equally and persisted in mature plants. In N-deficient conditions, sugarcane plants inoculated with A. diazotrophicus PAl5 generally grew better and had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
164
1
14

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(186 citation statements)
references
References 33 publications
(27 reference statements)
7
164
1
14
Order By: Relevance
“…Supply of nitrogen derived from fixation of atmospheric N 2 by grass endophytes, such as Gluconacetobacter diazotrophicus and Azoarcus sp. strain BH72, which has been shown to occur in sugarcane 3 and Kallar grass 2 , is a process of potential agronomical and ecological importance.…”
mentioning
confidence: 99%
“…Supply of nitrogen derived from fixation of atmospheric N 2 by grass endophytes, such as Gluconacetobacter diazotrophicus and Azoarcus sp. strain BH72, which has been shown to occur in sugarcane 3 and Kallar grass 2 , is a process of potential agronomical and ecological importance.…”
mentioning
confidence: 99%
“…The reduction in inoculation efficiency with successive harvests may be associated with N depletion in the soil, because some studies showed that inoculation has no influence on BNF in sugarcane (Schultz et al, 2012) and the yield increases after inoculation may be associated with the growthpromoting effects on the plant root system (Sevilla et al, 2001;Saravanan et al, 2007;Videira et al, 2012). In this case, if the benefit of inoculation is related to the increased use efficiency of plant-available soil N and the soil stock of available N decreases as the crops are being harvested, the efficiency of inoculation may decline over the years.…”
Section: Resultsmentioning
confidence: 99%
“…These results led to the conclusion that inoculation provided other benefits in sugarcane, which may be associated with the action of plant hormones synthesized by diazotrophic bacteria, phosphate and Zn solubilization, N retention and other essential nutrients in the rhizosphere. Sevilla et al (2001), comparing a strain of Gluconacetobacter with a nitrogenase negative (nif) mutant concluded that other factors, aside from BNF, may be responsible for the benefits resulting from inoculation. Several studies show that diazotrophic bacteria may act in promoting plant growth, mainly by changing the morphology of the root system, thus positively influencing the development and productivity of several crops of economic interest (Bashan et al, 2004;Somers et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained when the inoculation of the strain PAL5 was done in the presence of low amounts of nitrogen fertilizer (Moraes and Tauk-Tornisielo 1997). Proof that G. diazotrophicus fixes nitrogen was demonstrated by inoculation of micropropagated sugarcane plants with wild-type strain PAL5 and its nif minus mutant followed by measurement of 15 N 2 gas incorporated into the plant tissues (Sevilla et al 2001). Recent results have shown that sugarcane derives benefit from inoculation with a mixture of diazotrophic bacteria (Oliveira et al 2002).…”
Section: Inoculation Responsementioning
confidence: 99%